2021
DOI: 10.3399/bjgp.2021.0376
|View full text |Cite|
|
Sign up to set email alerts
|

Trends and clinical characteristics of COVID-19 vaccine recipients: a federated analysis of 57.9 million patients' primary care records in situ using OpenSAFELY

Abstract: BackgroundOn 8 December 2020 NHS England administered the first COVID-19 vaccination.AimTo describe trends and variation in vaccine coverage in different clinical and demographic groups in the first 100 days of the vaccine rollout.Design and settingWith the approval of NHS England, a cohort study was conducted of 57.9 million patient records in general practice in England, in situ and within the infrastructure of the electronic health record software vendors EMIS and TPP using OpenSAFELY.MethodVaccine coverage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 12 publications
(13 reference statements)
10
65
0
Order By: Relevance
“…There were significant differences in vaccine coverage by demographics, occupation setting, and staff group. Similar differences by factors such as age, sex, ethnicity, and occupation have been reported in other studies [ 14 , 15 , 16 ]. The differences in vaccine coverage that we reported among this population highlights the importance of an equitable vaccination program to all HCWs in Kuwait.…”
Section: Discussionsupporting
confidence: 88%
“…There were significant differences in vaccine coverage by demographics, occupation setting, and staff group. Similar differences by factors such as age, sex, ethnicity, and occupation have been reported in other studies [ 14 , 15 , 16 ]. The differences in vaccine coverage that we reported among this population highlights the importance of an equitable vaccination program to all HCWs in Kuwait.…”
Section: Discussionsupporting
confidence: 88%
“…However, adjusted associations in this study may still be biased by unmeasured confounding by patient characteristics that predict both vaccination and thromboses and that are difficult to ascertain in electronic health records. Examples include general health at the time of vaccination, and people at higher risk of thromboses (for example, with end-stage diseases) [ 18 ]. There were slightly lower postvaccination rates of the “negative control” outcome lower limb fracture in those aged ≥70 years, which are likely due to unmeasured confounding.…”
Section: Discussionmentioning
confidence: 99%
“…[32] Our survey also showed that those with lower levels of education and those belonging to the working class were less likely to be vaccinated, as found in a British survey covering the first 100 days of the vaccine rollout. [7] This could relate to the fact that members of the working classes have a perception of their body and their health that is more distant from medical diagnoses and recommendations than the upper class. [33] Racialised minorities, who had greater reluctance towards receiving a Covid-19 vaccine in France and in many countries [13,31] also appeared to be less likely to be vaccinated, as found in British and US surveys.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Making Covid-19 vaccines available does not necessarily lead to a very large population vaccine coverage, as shown by the percentages of people who are still not vaccinated in Western countries [4], even when these vaccines are free. Recent studies in the UK, in the US and in Norway [5][6][7][8][9][10] have shown that the most socially disadvantaged and racialised social groups are the least vaccinated. In light of their high risk of infection and mortality from Covid-19 [1], it appears all the more important to understand why they are less likely to be reached by Covid-19 vaccine programmes.…”
Section: Introductionmentioning
confidence: 99%